UNDERSTANDING THE AMERICAN DREAM FROM KARDASHIAN FAMILY THROUGH KEEPING UP WITH THE KARDASHIAN REALITY SHOW - Winda Eka Pahla Ayuningtyas; Munjid Achmad (CrossOver, 2021)
This study explains the relationship between the Kardashians and the American dream that has been championed by Americans to date. It is hypothesized that the more popular culture develops in our lives, the more it will affect the development of our culture. This can be seen from reality shows as a kind of popular culture that many people love. To find out how big the influence is, this study uses the Kardashians as an object to see how they and their reality show influence the community. By using textual analysis and utilizing materialism and capitalism as the theory, this research is expected to reveal the impact of the Kardashians on the development of the American dream. This study takes several texts from the reality show and analyzes them according to the theory used. Then, it is found that technological progress and economic growth, including commercial TV, expose Americans to materialism. The Kardashians commodified it into a captivating moneymaker that reality TV viewers aspire and inspire to consume. In addition, the materialism that they display on reality TV shows also thrives in viewers' minds from which they take advantage by commodifying every aspect of their lives as a form of product to sell so that viewers buy what they advertise.Â Keywords: American Dream, Keeping Up with The Kardashian, Materialism, Capitalism.